LncRNA AB209371 up-regulated Survivin gene by down-regulating miR-203 in ovarian carcinoma - Zi-Hui Zheng; Dong-Mei Wu; Shao-Hua Fan; Xin Wen; Xin-Rui Han; Shan Wang; Yong-Jian Wang; Zi-Feng Zhang; Qun Shan; Meng-Qiu Li; Bin Hu; Yuan-Lin Zheng; et al. (Journal of Ovarian Research, 2019)
Abstract AB209371 gene has been characterized as an oncogenic lncRNA in liver cancer. However, its involvement in ovarian carcinoma (OC) is unknown. In the present study, we analyzed the roles of AB209371 in OC. We found that AB209371 gene and Survivin gene were up-regulated in OC and positively correlated with OC development. AB209371 over-expression led to up-regulated Survivin in OC cells, while Survivin over-expression failed to affect AB209371. In addition, AB209371 over-expression led to down-regulated miR-203. However, miR-203 over-expression failed to affect AB209371, but down-regulated the expression of Survivin. In addition, over-expressions of AB209371 and Survivin resulted in the increased proliferation rate of OC cells. Over-expression MiR-203 played the opposite role and attenuated the effects of AB209371 over-expression. Therefore, AB209371 may down-regulate miR-203 to up-regulate Survivin, thereby promoting OC cell proliferation. Our study provided novel insights into the pathogenesis of OC.